Biochemical composition, bioactive components and antioxidant properties of desert and riverain legume plants: Rhynchosia minima and Lablab purpureus - El-Sayed, Magdi; Ahmed, Zainab G.; El-Shafy, Aya A. (Journal of Phytology, 2025)
Legumes are nutritionally dense, offering essential proteins and calories, and are especially important in meeting the dietary requirements of populations in developing regions. This study evaluates the nutritional and antioxidant properties of two species of legume plants inhabiting different habitats. Significant differences between Rhynchosia minima and Lablab purpureus seeds were found in proteins, carbohydrates, fibers, and fat content. The dried R. minima seeds showed the highest soluble and insoluble protein content (44.8 and 212 mg/g, respectively). Dried L. purpureus seeds contain more soluble carbohydrates (166 mg/g), while R. minima seeds contain more insoluble carbohydrates (230 mg/g). Fat content was higher in dried R. minima (2.84%), while fiber was higher in L. purpureus (65%). Phenolics, flavonoids, and antioxidant activities were also examined. Higher phenolic contents were represented in dried R. minima seeds of the methanolic extract, with a mean value of 103 mg/g. Also, the methanolic and water extracts of dried R. minima seeds generally contained significantly higher flavonoid content (16.8 and 18.2, respectively). The methanolic and aqueous extracts of dried and pre-matured R. minima seeds exhibited the highest antioxidant activity, achieving 92% DPPH radical scavenging at a concentration of 200 μg. In contrast, Lablab showed a maximum scavenging activity of only 56% at the same concentration, observed solely in the methanolic extract of fresh seeds. Total antioxidant activity and reducing power activity were also higher in water and methanolic extract of fresh R. minima seeds. High concentrations of protein, phenolics, and antioxidants were observed in R. minima, highlighting its suitability as a potential source of vital food constituents.